Detection and characterization of Aichi virus 1 in pediatric patients with diarrhea in Thailand - Chuchaona W. (2017)
© 2016 Wiley Periodicals, Inc. Kobuvirus is a newly discovered virus that belongs to the Kobuvirus genus in Picornaviridae family, which comprised of three species including Aichivirus A, Aichivirus B, and Aichivirus C. The kobuvirus isolated from human has been classified as Aichi virus 1 and belongs to Aichivirus A species. The present study aimed to assess the epidemiology and to perform molecular characterization of Aichi virus 1 in children admitted to hospitals with acute gastroenteritis in Chiang Mai, Thailand. A total of 923 fecal specimens collected from January, 2011 to December, 2013 were screened for the presence of Aichi virus 1 by RT semi-nested PCR. Out of 923 fecal specimens tested, Aichi virus 1 was detected with the prevalence of 2.6% (24/923). Of these, 0.3% (3/923) was genotype A and 2.3% (21/923) were genotype B. It is interesting to note that the genotype A showed the nucleotide sequence closely related to the Aichi virus reference strain isolated from sewage in Tunisia, while genotype B was most closely related to other human Aichi virus B reference strains. The results suggest that Aichi virus 1 of both genotypes A and B are circulating in pediatric patients in Thailand. J. Med. Virol. 89:234–238, 2017. © 2016 Wiley Periodicals, Inc.